Successful pilot test of rotating belt filters. Issue 4 (July 2016) - Jansen, Rob
Abstract : Aprovider of solids separation filter technology wanted to test its rotating belt filters as an alternative to primary sedimentation and sludge thickening units. A pilot application tested the filters' ability to remove suspended organics and divert them directly to anaerobic digesters.